Analisis Usaha Agroindustri Minuman Tradisional Kunyit Asam di Paon Jamu (Curcuma domestica Val. – Tamarindus indica L.) - Melia Dewi, Luh Putu; Mulyani, Sri; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): Maret, 2020)
Paon Jamu traditional beverage business is one of the traditional beverage businesses in the Tanjung Benoa area. Judging from the development of his business, Paon Jamu is one of the businesses that have just been established including many similar traditional beverage businesses. This study aims to determine the financial feasibility of the tamarind turmeric beverage business, determine the added value generated, determine the feasibility of a tamarind turmeric beverage business if there is an increase in operational costs and a decrease in revenue using a sensitivity analysis. Tamarind turmeric beverage business is feasible to run, the Net Present Value result is Rp. 6.144.470 for 300 ml packaging. Internal Rate of Return of 13% for 300 ml packaging and 14% indicates that the rate of return is greater than the specified bank interest rate. Payback Period for 2 years 5 months for 300 ml packaging. The B / C ratio is 1,42 for 300 ml packages. The added value of the business of turmeric acid is the added value obtained is Rp. 49.416 for a 300 ml package with a ratio of 47% The sensitivity analysis scenario shows that 300 ml package is sensitive to a 3 and 4% reduction in income in scenario II and III. Keywords: Tamarind turmeric, business analysis, Paon Jamu